High-leveling-property dry powder batch-scraping stone-like paint and preparation method thereof
By designing a high-leveling dry powder faux stone paint, and utilizing an optimized ratio of polymer and faux stone particles, the complex construction and environmental unfriendliness of existing faux stone paints are solved, achieving simplified construction, reduced costs, and improved weather resistance and waterproofing.
Patent Information
- Application Number
- CN202511372666.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-24
- Publication Date
- 2025-11-28
AI Technical Summary
The current application of faux stone paint is difficult, requiring multiple steps. Furthermore, traditional spraying and troweling methods for faux stone paint are challenging in terms of application and maintenance, resulting in high costs and environmental unfriendliness.
The high-leveling dry powder faux stone paint uses high-molecular polymer film-forming components and faux stone particle components in a ratio of 1:3~5. It uses lightweight inorganic materials to simplify the construction process, adds waterproofing agents and weather-resistant components to reduce VOC content, and adopts a troweling method.
It achieves simple construction, environmental protection, low cost, dense, waterproof, anti-corrosion, beautiful and weather-resistant paint film, reduces paint waste and pollution, has good coating durability, is easy to clean, and can achieve the ideal effect without multiple applications.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of architectural coatings. Specifically, this invention relates to a high-leveling dry powder troweling imitation stone paint and its preparation method. Background Technology
[0002] Currently, there are many types of faux stone paint on the market, and they are popular due to their artistic effect. Most of them are made of synthetic resin emulsions, additives, and colored sand, resulting in a high density that makes construction and maintenance difficult. Especially for the renovation of walls in older residential areas, traditional spraying and troweling methods for faux stone paint often require multiple construction steps to achieve the desired decorative effect. Summary of the Invention
[0003] To overcome the problems existing in the background technology, the present invention discloses a high-leveling dry powder troweling imitation stone paint and its preparation method. The high-leveling dry powder troweling imitation stone paint addresses the shortcomings of existing imitation stone paints by providing an imitation stone paint that is easy to apply, requires no protection, reduces costs, is energy-saving and environmentally friendly, and produces a dense, waterproof, corrosion-resistant, beautiful, and weather-resistant paint film.
[0004] To achieve the above objectives, the present invention is implemented through the following technical solution: The high-leveling dry powder trowel-applied stone-like paint is characterized in that the raw materials of the stone-like paint are a polymer film-forming component and a stone-like particle component, and the mass ratio of the polymer film-forming component to the stone-like particle component is 1:3~5. The polymer film-forming components are as follows by weight: base material: 300~500, thickener: 20~45, adhesive powder: 112.5~262.5, quick-setting agent: 74~220, dispersant: 7.5~35, pH adjuster: 7.5~15, dry powder defoamer: 7.5~15, water-reducing agent: 15~40, waterproofing agent: 75~250; The imitation stone particles are composed of the following parts by weight: white: 500~800; colored sand: 200~500.
[0005] Preferably, the polymer film-forming components are as follows: base material: 450 parts, thickener: 30 parts, adhesive powder: 200.5 parts, quick-setting agent: 150 parts, dispersant: 25.5 parts, pH adjuster: 10.5 parts, dry powder defoamer: 10.5 parts, water-reducing agent: 25.5 parts, and waterproofing agent: 200.5 parts; the stone-like particle components are as follows: white sand: 750 parts, colored sand: 300 parts.
[0006] Preferably, the base material is two or more of silicate cement, white cement, high-alumina cement, phenolic resin, and epoxy resin; the thickener is three or more of hydroxyethyl cellulose (30,000 viscosity), hydroxypropyl methyl cellulose (200,000 viscosity), hydroxyethyl methyl cellulose (30,000 viscosity), organo-bentonite, and aluminum silicate; the adhesive powder is one or more of acrylic redispersible latex powder, polyvinyl alcohol 2488, polyvinyl alcohol 1788, 509 adhesive powder, and 603 adhesive powder; the quick-setting agent is one or more of sodium silicate, sodium sulfate, and sodium fluorosilicate; the dispersant is one or more of sodium polyacrylate and sodium hexametaphosphate; the pH adjuster is one or more of phosphoric acid, tartaric acid, malic acid, and citric acid; the water-reducing agent is one or more of lignin sulfonate water-reducing agent, melamine water-reducing agent, and polycarboxylate water-reducing agent; and the waterproofing agent is one or more of zinc stearate, potassium silicate, polyoxyethylene wax, potassium methylsilicate, and aluminum sulfate.
[0007] Preferably, the base material, thickener, adhesive powder, quick-setting agent, dispersant, pH adjuster, dry powder defoamer, water-reducing agent, and waterproofing agent in the polymer film-forming component are all in powder or fine granular form.
[0008] Preferably, the thickener is used in an amount of 1% to 3% of the polymer film-forming component; the adhesive powder is used in an amount of 15% to 25% of the polymer film-forming component; the quick-setting agent is used in an amount of 8% to 15% of the polymer film-forming component; the water-reducing agent is used in an amount of 1.5% to 2.5% of the polymer film-forming component, and the remainder is a mixture of base material, dispersant, pH adjuster, dry powder defoamer, and waterproofing agent.
[0009] As a preferred option, the white sand is one or three of the following: 10-20 mesh snowflake white sand, 40-80 mesh snowflake white sand, and 80-120 mesh snowflake white sand; Preferably, the colored sand is one or more of the following: 10-20 mesh liver red colored sand, 40-80 mesh liver red colored sand, 10-20 mesh diamond black colored sand, 40-80 mesh diamond black colored sand, and 80-120 mesh diamond black colored sand.
[0010] As a preferred embodiment, the method for preparing the high-leveling dry powder trowel-applied stone-like paint includes the following steps: 1) Take the weight of the polymer film-forming component of the formula and put it into a mixer and stir for 1-2 hours to obtain a semi-finished product, then seal it for later use. 2) Take sand of the same weight as the imitation stone particle component, add it to the mortar dry powder mixer and mix for 0.5-1 hour to obtain a uniform semi-finished product, then seal it for later use.
[0011] 3) Mixing and stirring: Take the polymer film-forming component and the imitation stone particles prepared in step 1) and step 2) at a ratio of 1:3~5, add them to the finished product dry powder mixer, stir evenly, and then package to obtain the finished product.
[0012] Preferably, in step 1), a polymer dry powder mixer is used for mixing; in step 2), a mortar dry powder mixer is used for mixing; and in step 3), a finished product dry powder mixer is used for mixing.
[0013] As a preferred method: when using the dry powder imitation stone paint, mix the dry powder imitation stone paint with neutral purified water at a ratio of 1:0.35, let it stand for 10 minutes, stir again, and then apply it to the wall.
[0014] The beneficial effects of this invention are: (1) The raw materials of the faux stone paint are a polymer film-forming component and a faux stone particle component, with a mass ratio of 1:3~5. The polymer film-forming component and the faux stone particle component are mixed and stirred evenly to obtain dry powder faux stone paint. The dry powder faux stone paint has a light weight and high weather resistance. The dry powder faux stone paint adopts a troweling construction method, which simplifies the construction process, reduces paint splashing caused by spraying, reduces paint waste and environmental pollution, and reduces construction costs.
[0015] (2) The drying time of the dry powder applied imitation stone paint is less than 3 hours. After at least five freeze-thaw cycles, the bonding strength is 0.2 MPa. The artificial weathering test result is that the coating does not crack, blister, or peel after 600 hours. The chalking level is 0, the discoloration level is ≤1, and there are no cracks in the diameter of 50 mm. It has good flexibility. After the dry powder applied imitation stone paint is applied, the paint film is smooth, not easy to be contaminated with dust, and easy to clean. It has high density and a waterproofing agent is added to improve its waterproof performance. It does not leave trowel marks and can achieve the ideal smooth effect without multiple applications or sanding.
[0016] (3) The dry powder troweling imitation stone paint is basically made of inorganic materials, which is anti-aging and weather-resistant; the VOC content is extremely low and it is green and environmentally friendly; the dry powder troweling imitation stone paint does not use color paste or color powder for color matching, and the color matching is all done with colored sand. After the paint film dries, it shows natural color and does not change color or fade. Detailed Implementation
[0017] To make the performance and characteristics of the high-flowability dry powder coating for faux stone of the present invention clearer, the present invention will be further described in detail with reference to the following examples.
[0018] Example 1: Preparation of dry powder coating for imitation stone 1) Mix silicate cement and epoxy resin to obtain a mixture of 450 parts by weight; mix hydroxyethyl cellulose (30,000 viscosity) and aluminum silicate to obtain a mixture of 30 parts by weight; mix acrylic redispersible latex powder, polyvinyl alcohol 2488, and 603 adhesive powder to obtain a mixture of 200.5 parts by weight; take 150 parts by weight of sodium silicate; take 25.5 parts by weight of sodium polyacrylate; take 10.5 parts by weight of phosphoric acid; take 25.5 parts by weight of lignin sulfonate water-reducing agent; mix zinc stearate and potassium silicate to obtain a mixture of 200.5 parts by weight; take 10.5 parts by weight of dry powder defoamer; put the above-mentioned materials into a polymer dry powder mixer and stir for 2 hours to obtain a polymer film-forming component for later use.
[0019] 2) Mix 70-mesh snowflake white sand and 100-mesh snowflake white sand to obtain 750 parts by weight of the mixture; mix 20-mesh liver red colored sand, 70-mesh liver red colored sand and 100-mesh diamond black colored sand to obtain 300 parts by weight of the mixture; put the above-mentioned materials into a mortar dry powder mixer and stir for 2 hours to obtain the imitation stone particle component for later use. 3) Add the polymer film-forming component and the stone-like particle component to the finished dry powder mixer at a mass ratio of 1:3 and stir for 2 hours until uniform to obtain a high leveling dry powder troweling stone-like paint. 4) When using dry powder imitation stone paint, mix the dry powder imitation stone paint with neutral purified water at a ratio of 1:0.35, let it stand for 10 minutes, stir again, and then apply it to the wall.
[0020] Example 2: Preparation of dry powder coating for imitation stone 1) Mix high-alumina cement and phenolic resin, taking 450 parts by weight of the mixture; mix hydroxypropyl methylcellulose (200,000 viscosity), organobentonite, and aluminum silicate, taking 30 parts by weight of the mixture; mix acrylic redispersible latex powder, polyvinyl alcohol 1788, and 509 adhesive powder, taking 200.5 parts by weight of the mixture; take 150 parts by weight of sodium sulfate; mix sodium polyacrylate and sodium hexametaphosphate, taking 25.5 parts by weight of the mixture; take 10.5 parts by weight of tartaric acid; take 25.5 parts by weight of melamine water-reducing agent; mix zinc stearate, potassium silicate, and polyoxyethylene wax, taking 200.5 parts by weight of the mixture; take 10.5 parts by weight of dry powder defoamer; put the above-mentioned materials into a polymer dry powder mixer and stir for 2 hours to obtain a high molecular weight polymer film-forming component for later use.
[0021] 2) Mix 70-mesh snowflake white sand and 100-mesh snowflake white sand to obtain 750 parts by weight of the mixture; mix 20-mesh liver red colored sand, 70-mesh liver red colored sand and 100-mesh diamond black colored sand to obtain 300 parts by weight of the mixture; put the above-mentioned materials into a mortar dry powder mixer and stir for 2 hours to obtain the imitation stone particle component for later use. 3) Add the polymer film-forming component and the stone-like particle component to the finished dry powder mixer at a mass ratio of 1:3 and stir for 2 hours until uniform to obtain a high leveling dry powder troweling stone-like paint. 4) When using dry powder imitation stone paint, mix the dry powder imitation stone paint with neutral purified water at a ratio of 1:0.35, let it stand for 10 minutes, stir again, and then apply it to the wall.
[0022] Example 3: Preparation of dry powder coating for imitation stone 1) Mix high-alumina cement and epoxy resin, taking 450 parts by weight of the mixture; mix hydroxypropyl methylcellulose (30,000 viscosity), organobentonite, and aluminum silicate, taking 30 parts by weight of the mixture; mix acrylic redispersible latex powder, polyvinyl alcohol 2488, and 509 adhesive powder, taking 200.5 parts by weight of the mixture; mix sodium silicate, sodium sulfate, and sodium fluorosilicate, taking 150 parts by weight of the mixture; mix sodium polyacrylate and sodium hexametaphosphate, taking 2... 5.5 parts by weight of the mixture; 10.5 parts by weight of citric acid; 25.5 parts by weight of the mixture of lignin sulfonate water-reducing agent, melamine water-reducing agent, and polycarboxylate water-reducing agent; 200.5 parts by weight of the mixture of polyoxyethylene wax, potassium methylsilicate, and aluminum sulfate; 10.5 parts by weight of dry powder defoamer; put the above-mentioned materials into a polymer dry powder mixer and stir for 2 hours to obtain a polymer film-forming component for later use.
[0023] 2) Mix 70-mesh snowflake white sand and 100-mesh snowflake white sand to obtain 750 parts by weight of the mixture; mix 20-mesh liver red colored sand, 70-mesh liver red colored sand and 100-mesh diamond black colored sand to obtain 300 parts by weight of the mixture; put the above-mentioned materials into a mortar dry powder mixer and stir for 2 hours to obtain the imitation stone particle component for later use. 3) Add the polymer film-forming component and the stone-like particle component to the finished dry powder mixer at a mass ratio of 1:3 and stir for 2 hours until uniform to obtain a high leveling dry powder troweling stone-like paint. 4) When using dry powder imitation stone paint, mix the dry powder imitation stone paint with neutral purified water at a ratio of 1:0.35, let it stand for 10 minutes, stir again, and then apply it to the wall.
[0024] Example 4: Preparation of dry powder coating for imitation stone 1) Mix high-alumina cement and epoxy resin to obtain a mixture of 450 parts by weight; mix hydroxypropyl methylcellulose (30,000 viscosity), organobentonite, and aluminum silicate to obtain a mixture of 30 parts by weight; mix acrylic redispersible latex powder, polyvinyl alcohol 2488, and 509 powder to obtain a mixture of 200.5 parts by weight; mix sodium silicate, sodium sulfate, and sodium fluorosilicate to obtain a mixture of 150 parts by weight; mix sodium polyacrylate and sodium hexametaphosphate to obtain a mixture of 25 parts by weight. Take 5 parts by weight of the mixture; take 10.5 parts by weight of citric acid; mix lignin sulfonate water-reducing agent, melamine water-reducing agent and polycarboxylate water-reducing agent, and take 25.5 parts by weight of the mixture; mix polyoxyethylene wax, potassium methylsilicate and aluminum sulfate, and take 200.5 parts by weight of the mixture; take 10.5 parts by weight of dry powder defoamer; put the above-mentioned materials into a polymer dry powder mixer and stir for 2 hours to obtain a polymer film-forming component for later use.
[0025] 2) Mix 70-mesh snowflake white sand and 100-mesh snowflake white sand to obtain 750 parts by weight of the mixture; mix 20-mesh liver red colored sand, 70-mesh liver red colored sand and 100-mesh diamond black colored sand to obtain 300 parts by weight of the mixture; put the above-mentioned materials into a mortar dry powder mixer and stir for 2 hours to obtain the imitation stone particle component for later use. 3) Add the polymer film-forming component and the stone-like particle component to the finished dry powder mixer at a mass ratio of 1:3 and stir for 2 hours until uniform to obtain a high leveling dry powder troweling stone-like paint. 4) When using dry powder imitation stone paint, mix the dry powder imitation stone paint with neutral purified water at a ratio of 1:0.35, let it stand for 10 minutes, stir again, and then apply it to the wall.
[0026] The dry powder troweling imitation stone paints prepared in Examples 1, 2, 3, and 4 were collected. 500 grams of each of Examples 1, 2, 3, and 4 were taken and tested according to the external wall type test data of JG / T 24-2018. The test results are shown in Table 1. The wall application effect of the dry powder troweling imitation stone paints prepared in Examples 1, 2, 3, and 4 was compared and recorded.
[0027] In summary, the dry powder trowel-applied stone-like paints prepared in Examples 1, 2, 3, and 4 all met the test indicators. The drying time was less than 3 hours. After at least five freeze-thaw cycles, the bonding strength was 0.2 MPa. The artificial weathering resistance test results showed that the coating did not crack, blister, or peel after 600 hours, with chalking at level 0 and discoloration ≤ level 1. After application, the dry powder trowel-applied stone-like paint left no cracks on a 50mm diameter wall. The paint also exhibited good flexibility. Therefore, the dry powder trowel-applied stone-like paints prepared in Examples 1, 2, 3, and 4 used raw materials that improved leveling properties. After trowel application, the paint film was smooth, not easily attracting dust, and easy to clean. It had high density and contained a waterproofing agent to improve its waterproof performance. It left no trowel marks and achieved an ideal smooth effect without multiple applications or sanding.
[0028] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made to it in form and detail without departing from the scope defined by the claims of the present invention.
Claims
1. A high-leveling dry powder coating for imitation stone, characterized in that, The raw materials for the faux stone paint are a polymer film-forming component and a faux stone particle component, with a mass ratio of polymer film-forming component to faux stone particle component of 1:3~5. The polymer film-forming components are as follows by weight: base material: 300-500 parts, thickener: 20-45 parts, adhesive powder: 112.5-262.5 parts, quick-setting agent: 74-220 parts, dispersant: 7.5-35 parts, pH adjuster: 7.5-15 parts, dry powder defoamer: 7.5-15 parts, water-reducing agent: 15-40 parts, waterproofing agent: 75-250 parts; The imitation stone particles are composed of the following parts by weight: White sand: 500-800 parts; Colored sand: 200-500 parts.
2. The high-leveling dry powder coating for imitation stone as described in claim 1, characterized in that: The preferred polymer film-forming components are as follows (parts by weight): base material: 450 parts, thickener: 30 parts, adhesive powder: 200.5 parts, quick-setting agent: 150 parts, dispersant: 25.5 parts, pH adjuster: 10.5 parts, dry powder defoamer: 10.5 parts, water-reducing agent: 25.5 parts, and waterproofing agent: 200.5 parts. The preferred composition of the imitation stone particles is as follows: white sand: 750 parts, colored sand: 300 parts.
3. The high-leveling dry powder coating for imitation stone as described in claim 1, characterized in that: The base material is two or more of the following: silicate cement, white cement, high-alumina cement, phenolic resin, and epoxy resin. The thickener is one or more of the following: hydroxyethyl cellulose with a viscosity of 30,000, hydroxypropyl methyl cellulose with a viscosity of 200,000, hydroxyethyl methyl cellulose with a viscosity of 30,000, organic bentonite, and aluminum silicate. The adhesive powder is one or more of the following: acrylic redispersible latex powder, polyvinyl alcohol 2488, polyvinyl alcohol 1788, 509 adhesive powder, and 603 adhesive powder; The quick-setting agent is one or more of sodium silicate, sodium sulfate, and sodium fluorosilicate. The dispersant is one or more of sodium polyacrylate and sodium hexametaphosphate. The pH adjuster is one or more of phosphoric acid, tartaric acid, malic acid, and citric acid. The water-reducing agent is one or more of the following: lignin sulfonate water-reducing agent, melamine water-reducing agent, and polycarboxylate water-reducing agent; The waterproofing agent is one or more of the following: zinc stearate, potassium silicate, polyoxyethylene wax, potassium methylsilicate, and aluminum sulfate.
4. The high-leveling dry powder coating for imitation stone as described in claim 1, characterized in that: The polymer film-forming components, including the base material, thickener, adhesive powder, quick-setting agent, dispersant, pH adjuster, dry powder defoamer, water-reducing agent, and waterproofing agent, are all in powder or fine granule form.
5. The high-leveling dry powder coating for imitation stone as described in claim 1, characterized in that: The amount of thickener used accounts for 1% to 3% of the polymer film-forming component; the amount of adhesive powder used accounts for 15% to 25% of the polymer film-forming component; the amount of quick-setting agent used accounts for 8% to 15% of the polymer film-forming component; the amount of water-reducing agent used accounts for 1.5% to 2.5% of the polymer film-forming component, and the remainder is a mixture of base material, dispersant, pH adjuster, dry powder defoamer, and waterproofing agent.
6. The high-leveling dry powder coating for imitation stone as described in claim 1, characterized in that: The white sand is one or three of the following: 10-20 mesh snowflake white sand, 40-80 mesh snowflake white sand, and 80-120 mesh snowflake white sand.
7. The high-leveling dry powder coating for imitation stone as described in claim 1, characterized in that: The colored sand is one or more of the following: 10-20 mesh liver red colored sand, 40-80 mesh liver red colored sand, 10-20 mesh diamond black colored sand, 40-80 mesh diamond black colored sand, and 80-120 mesh diamond black colored sand.
8. The high-leveling dry powder coating for imitation stone as described in claim 1, characterized in that: The preparation method of the high-leveling dry powder trowel-applied stone-like paint includes the following steps: 1) Take the weight of the formula of the polymer film-forming component and put it into a mixer and stir for 1-2 hours to obtain a semi-finished product, then seal it for later use. 2) Take the sand of the imitation stone particle component by weight, add it to the mortar dry powder mixer and stir for 0.5-1 hour to obtain a uniform semi-finished product, then seal it for later use. 3) Mixing and stirring: Take the polymer film-forming component and the imitation stone particles prepared in step 1) and step 2) at a ratio of 1:3~5, add them to the finished product dry powder mixer, stir evenly, and then package to obtain the finished product.
9. The high-leveling dry powder coating for imitation stone as described in claim 8, characterized in that: In step 1), a polymer dry powder mixer is used for mixing; in step 2), a mortar dry powder mixer is used for mixing; and in step 3), a finished product dry powder mixer is used for mixing.
10. The high-leveling dry powder coating for imitation stone as described in claim 1, characterized in that: When using the dry powder imitation stone paint, mix the dry powder imitation stone paint with neutral purified water at a ratio of 1:0.35, let it stand for 10 minutes, stir again, and then apply it to the wall.